2019
DOI: 10.5144/0256-4947.2019.345
|View full text |Cite
|
Sign up to set email alerts
|

Trends in thyroid carcinoma among thyroidectomy patients: a 12-year multicenter study

Abstract: BACKGROUND: Thyroid malignancy, the most diagnosed cancer of the endocrine system, represents 2% of all malignancies worldwide. The increasing incidence of thyroid cancer has been linked to the increasing sensitivity of modern diagnostic methods which overdiagnosis small thyroid tumors.OBJECTIVES: Assess the distribution and trends in thyroid cancer among thyroidectomy patients.DESIGN: Descriptive, based on medical record review.SETTINGS: Two tertiary care centers in Riyadh.PATIENTS AND METHODS: We included pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 14 publications
2
8
0
Order By: Relevance
“…Median age of the study population was 39.2 years. This finding is similar to studies from other Middle Eastern ethnicities ( 24 27 ), but lower than that seen in Western population ( 28 ). This most likely represents the inherent aggressive nature of PTC in the Middle Eastern ethnicity.…”
Section: Discussionsupporting
confidence: 88%
“…Median age of the study population was 39.2 years. This finding is similar to studies from other Middle Eastern ethnicities ( 24 27 ), but lower than that seen in Western population ( 28 ). This most likely represents the inherent aggressive nature of PTC in the Middle Eastern ethnicity.…”
Section: Discussionsupporting
confidence: 88%
“…We are anticipating that the trend in Saudi Arabia will also exhibit a similar pattern in the upcoming few years, especially with the availability of more sophisticated medical investigations and as more Saudis gain access to private insurance. Of note, a recent Saudi study from Riyadh analysing TC trends concluded that the incidence of TC microcarcinomas has increased in the previous seven years in comparison to a steady overall TC incidence [17].…”
Section: Figure 3: Correlation Between the Year Of Diagnosis And The Tumor Size Discussionmentioning
confidence: 99%
“…PTC is common in Middle Eastern population with favorable long term prognosis ( 4 , 28 , 29 ). The fundamental therapy of PTC is surgery.…”
Section: Discussionmentioning
confidence: 99%